Handbook of prevention and treatment with children and adolescents intervention in the real world context (Wiley, 1997)
The book begins with a close examination of the destructive influence of poverty and other social ills on child development and moves on to discuss specific intervention formats and settings - from individual treatment to school and community-based programs. The second half of the book offers an extended exploration of particular problem areas and psychiatric disorders. A review of early intervention and preventive approaches for such behavioral issues as substance abuse, antisocial behavior, and sexually transmitted diseases is followed by recommendations for treatment of specific psychiatric disorders such as depression, anxiety, eating disorders, and posttraumatic stress